Rice-Fish Culture and its Potential in Rural Development: A Lesson from Apatani Farmers, Arunachal Pradesh, India - Saikia, SK; Das, DN (Journal of Agriculture & Rural Development, 2008)
Rice-based fish farming, though, inevitable as a mean of double crop production from the unit land, is often proves as cost-effective practice for marginal and poor farmers. The lack of adequate knowledge and support to farmers keep them away from the benefits of rice-based fish farming. The novel technique adopted by Apatani farmers in Lower Subansiri district of Arunachal Pradesh, India reduces the knowledge gap to achieve optimum benefit from such farming practice. The farmers enjoy a fish production of 500 kg per hactor per year without providing any supplementary feed to the fish stocked in their rice-fields. The economic return of the farmers was estimated up to 65.8% per annum from their rice-fish integrated fields. The system of rice-based fish farming by Apatani farmers has, therefore, bears immense potentiality to be recognized as low cost and sustainable farming practice and could be a significant breakthrough for poor and marginal farmers of the rest of the World. DOI: http://dx.doi.org/10.3329/jard.v6i1.1667 J Agric Rural Dev 6(1&2), 125-131, June 2008